THE ENERGY SECTOR OF UZBEKISTAN: PRESENT STATE AND PROBLEMS - KENISARIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2004)
The entire fuel and energy complex of Uzbekistan belongs to the state: the oil and gas branch is controlled by the National Holding Uzbekneftegaz; coal, by the Ugol firm, one of the companies that make up the State Joint-Stock Company called Uzbekenergo that is responsible for the power production sector. In other words, until recently the fuel and energy complex that remained a vertically arranged and rigidly integrated system it had been under Soviet power was never affected by the market reforms going on in other spheres. Presidential decree No. 2812 of 22 February 2001 On Deepening Economic Reforms in the Energy Sphere of the Republic of Uzbekistan opened an era of changes in this economic branch.